A shallow-water oxygen minimum zone in an oligotrophic Tonian basin - Yunpeng Sun; Wei Wang; Xianguo Lang; Chengguo Guan; Qing Ouyang; Ke Pang; Guangjin Li; Yongliang Hu; Hongyi Shi; Xianye Zhao; Chuanming Zhou (Nature Communications)
Abstract The Tonian Period (1000–720 Ma) bore witness to the transition from a prokaryote-dominated marine ecosystem to one characterized by the proliferation of eukaryotes. This fundamental shift has generally been attributed to evolving marine redox states. Here, we present sedimentological and geochemical analyses of the early Tonian Huainan, Feishui, and Huaibei groups in the Xuhuai basin of the North China craton. Multiple redox proxies show consistent, water depth-dependent variations across the Xuhuai basin. Excess barium contents and Ba/Al ratios further highlight spatial variations in primary productivity which ultimately regulate basinal redox structures. We propose that a shallow-water oxygen minimum zone sandwiched between the oxic/suboxic mid-depth and surface layer water masses occur in the oligotrophic Xuhuai basin, which is analogous to, but much shallower than modern oxygen minimum zones. Such marine redox architectures may benefit the maintenance of a bioavailable nitrate reservoir in the ocean, foreboding the subsequent expansion of eukaryotes.